Peer Feedback Technique in Writing Descriptive Text: Is it effective? - Maharani, Fallah; Rofiqoh; Anggreni, Afrilia; Budi (Institut Agama Islam Negeri Palopo, 2024)
The aim of this study was to prove whether the implementation of Peer Feedback could improve students’ writing skills. The design of this study was quasy-experimental. The population was the seventh-grade of SMP Negeri 1 Palu, which consisted of 326 students and purposive random sampling was used to decide Experimental and control group. The researchers used test to collect the data in term of pretest and posttest. However, only the experimental class got treatment of peer feedback while the control group got other treatments. Organization, Content, vocabulary, grammar, and mechanic were focus of this research. After implementing peer feedback, the result presents that the students mean score of the experimental group (81.55) on the post-test is higher than the score of the control group. (71.96). It was different from the result of pretest, which the mean score of control group was statistically higher than experimental class. Furthermore, the significance value (2-tailed) is 0.00 lower than 0.05. Thus, it can be interpreted that peer feedback technique effectively improve students’ writing skill. As a conclusion, peer feedback is a recommended technique in teaching writing.